Ultraviolet–Visible (UV-Vis) and Fluorescence Spectroscopic Investigation of the Interactions of Ionic Liquids and Catalase. Issue 11 (November 2016) - Dong, Xing; Fan, Yunchang; Yang, Peng; Kong, Jichuan; Li, Dandan; Miao, Juan; Hua, Shaofeng; Hu, Chaobing
The inhibitory effects of nine ionic liquids (ILs) on the catalase activity were investigated using fluorescence, absorption ultraviolet-visible spectroscopy. The interactions of ILs and catalase on the molecular level were studied. The experimental results indicated that ILs could inhibit the catalase activity and their inhibitory abilities depended on their chemical structures. Fluorescence experiments showed that hydrogen bonding played an important role in the interaction process. The inhibitory abilities of ILs on catalase activity could be simply described by their hydrophobicity and hydrogen bonding abilities. Unexpected less inhibitory effects of trifluoromethanesulfonate (TfO − ) might be ascribed to its larger size, which makes it difficult to go through the substrate channel of catalase to the active site.